2018
DOI: 10.1111/jse.12312
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics and dispersal patterns of Brassicaceae around the Qinghai–Tibet Plateau

Abstract: Brassicaceae, one of the most diverse and economically valuable plant families, is distributed all over the world. Previous studies have suggested that Brassicaceae originated and diversified in the Old World. In this study, the phylogenetic relationships of 17 tribes of Brassicaceae from the Qinghai-Tibet Plateau (QTP) and adjacent areas were investigated using nuclear ribosomal internal transcribed spacer (nrITS) and chloroplast DNA sequence data (rbcL and petB-petD) with maximum likelihood, maximum parsimon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Our nrDNA phylogeny recovered four monophyletic clades (namely clades a, b, c, and d) in which the intratribal relationships were generally highly supported. Interestingly, the unsolved tribe Megacarpaeeae in target captured analysis (Huang et al, 2015; Nikolov et al, 2019) was well resolved as sister to the subclade comprising Stevenieae and Arabideae (BIPP = 1.0) here, which was congruent with the ITS phylogeny by Qian et al (2018). Our results indicated that the full‐length nrDNA cistron sequences might contain abundant phylogenetic informative sites and have the potential to improve relationships at intratribal and lower taxonomic ranks of core Brassicaceae.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our nrDNA phylogeny recovered four monophyletic clades (namely clades a, b, c, and d) in which the intratribal relationships were generally highly supported. Interestingly, the unsolved tribe Megacarpaeeae in target captured analysis (Huang et al, 2015; Nikolov et al, 2019) was well resolved as sister to the subclade comprising Stevenieae and Arabideae (BIPP = 1.0) here, which was congruent with the ITS phylogeny by Qian et al (2018). Our results indicated that the full‐length nrDNA cistron sequences might contain abundant phylogenetic informative sites and have the potential to improve relationships at intratribal and lower taxonomic ranks of core Brassicaceae.…”
Section: Discussionsupporting
confidence: 84%
“…As indicated in Fig. 3, the most remarkably incongruent relationships were those involving the LII, which consisted of only four tribes initially (Zhao et al, 2010; Franzke et al, 2011; Huang et al, 2015; Qian et al, 2018; Nikolov et al, 2019). Controversial results from previous studies were generally attributed to homoplasy in morphology (e.g., Al‐Shehbaz et al, 2006; Beilstein et al, 2006; Al‐Shehbaz, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Intergenic spacer (IGS) regions exhibited the highest average nucleotide diversity, followed by intronic and coding regions. The finding that protein-coding genes have little nucleotide diversity supports the assumption that they are more conserved in Brassicaceae species [3,12,22,93,94]. Nucleotide diversity varies from 0.00085 to 0.08516; such low nucleotide diversity values indicate plastome structure conservation in clade C members, and a lower rate of nucleotide diversity has been seen in numerous other plants [95][96][97][98].…”
Section: Discussionmentioning
confidence: 67%
“…The estimate of net diversification rates between 11.8 and 8 Ma is 1.03 species per million years (species/Myr). This rate is higher than in many documented examples of fast plant radiations in Southwest China, including of alpine bamboos (0.75 species/Myr; Poaceae; Ye et al 2019), tribe Anastaticeae (0.17 species/Myr; Brassicaceae; Qian et al 2018 ), Hirculoideae and Kabschia (0.455 and 0.471 species/Myr; Saxifragaceae; Ebersbach et al 2017 ), and 17 angiosperm clades (ca. 0.12 species/Myr; Xing and Ree 2017 ); or in other biodiversity hotpots; for example, Fosterella within the Andean Mountains (0.40 species/Myr; Bromeliaceae; Wagner et al 2013 ).…”
Section: Discussionmentioning
confidence: 72%